Presence of Legionella spp. in Hot Water Networks of Different Italian Residential Buildings: A Three-Year Survey - Totaro, Michele (Int J Environ Res Public Health, 2017)
Although the European reports highlight an increase in community-acquired Legionnaires’ disease cases, the risk of Legionella spp. in private houses is underestimated. In Pisa (Italy) we performed a three-year survey on Legionella presence in 121 buildings with an independent hot water production (IB); 64 buildings with a central hot water production (CB); and 35 buildings with a solar thermal system for hot water production (TB). From all the 220 buildings Legionella spp. was researched in two hot water samples collected either at the recirculation point or on the first floor and on the last floor, while the potable water quality was analysed in three cold water samples collected at the inlet from the aqueduct network, at the exit from the autoclave, and at the most remote tap. Legionella pneumophila sg1, Legionella pneumophila sg2–16, and non-pneumophila Legionella species were detected in 26% of the hot water networks, mostly in CB and TB. In these buildings we detected correlations between the presence of Legionella and the total chlorine concentration decrease and/or the increase of the temperature. Cold water resulted free from microbiological hazards, with the exception of Serratia liquefaciens and Enterobacter cloacae isolated at the exit from two different autoclaves. We observed an increase in total microbial counts at 22 °C and 37 °C between the samples collected at the most remote taps compared to the ones collected at the inlet from the aqueduct. The study highlights a condition of potential risk for susceptible categories of population and supports the need for measures of risk assessment and control.